A Simulation-Based Optimization Method for the Integrative Design of the Building Envelope. (November 2015) - Ferrara, Maria; Filippi, Marco; Sirombo, Elisa; Cravino, Vittorio
Abstract: An effective design of green buildings requires a process of optimization to meet all the sustainability goals through an integrative design approach. The research focuses on the development of a replicable methodology for the optimization of the building features that affects specifically the energy demand and indoor comfort conditions. Optimal design solutions are found following two steps: minimization of the total energy demand for heating, cooling and lighting coupling TRNSYS ®, a dynamic simulation software, and GenOpt ®, a Generic optimization program; a post-processing analysis considering thermal and visual comfort aspects. This optimization methodology was conducted on a school classroom case-study.